La Red de Escuelas de Música de Medellín, un espacio para la construcción de la identidad de los adolescentes participantes (2017)
ABSTARCT: In this article, the main findings of the research study “Medellin’s Schools of Music Network, a space for identity construction of teenage participants” are presented. Its main objective was to describe, from these teenagers’ perspective, how does the Network help them to construct their identity. This research was conducted with a qualitative methodology based on symbolic interactionism. Data were collected through eight individual and six focusgroup interviews. Findings revealed that teenage participants see the Network as a second family. Likewise, they see it as a space where they not only learn about music but can also develop different skills. Moreover, the Network allow them to recognize themselves and others and construct a life project different to the models they see around their neighborhoods, a salient theme in their narratives.